The Structure of Regional Original Revenue and Its Effect on Economic Growth: Facts from Regencies and Cities in Central Jawa - Wahyudi Susanto; Catur Sugianto (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
This study aims to determine the structure of Regional Original Revenue (PAD) in its effect on economic growth. The data used are panel data from 35 regencies and cities in Central Java for the period 2005 to 2015. Data are taken from the Regencies and Cities Financial Audit Results Reports in Central Java. Data analysis technique uses Panel Vector Error Correction Model (PVECM) and Panel Granger Causality Test to determine the relationship between economic growth and PAD components, namely regional tax revenue, regional retribution revenue, regional wealth revenue, and other legitimate revenue. The results of this study found a one-way causality relationship from tax revenue to economic growth. There is a two-way relationship occurs between retribution revenue and economic growth. There is a one-way relationship from the regional wealth revenue to economic growth. There is a one-way relationship from the total regional original revenue (PAD) to economic growth. There is no relationship between other legitimate revenue and economic growth. In the short run, the economic growth over a given period was positively and significantly affected by the tax revenue, retribution revenue and regional original revenue (PAD) of the previous year, while regional wealth revenue has a negative and significant effect on economic growth. In the long run, tax revenue, retribution revenue and regional original revenue (PAD) effect by positively and significantly to economic growth, while regional wealth revenue has a negative and significant effect on economic growth.